2013
DOI: 10.3856/vol41-issue4-fulltext-2
|View full text |Cite
|
Sign up to set email alerts
|

Amphidromy in shrimps: a life cycle between rivers and the sea

Abstract: ABSTRACT. Amphidromy is a diadromous life history pattern, common in tropical and subtropical freshwater caridean shrimps, in which adults live, breed and spawn small-sized embryos in freshwater but have extended larval development (ELD) in marine waters. Most completely freshwater species spawn large embryos with either direct or abbreviated larval development (ALD). An important benefit of amphidromy is dispersal among river systems via marine larvae, which increases their access to alternative habitats. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 74 publications
2
111
0
10
Order By: Relevance
“…These authors observed ovigerous females carrying egg at all stages in all the study sites during the reproductive season with no records of reproductive females disappearing far from the coast, which means there was no reproductive migration towards estuaries to hatch larvae. Other evidence relies on the presence of the ovigerous females during high water or rainy months in the river inhabited by adults, which is a reverse pattern from the pattern described by Bauer (2013).…”
Section: Reproductionmentioning
confidence: 94%
See 2 more Smart Citations
“…These authors observed ovigerous females carrying egg at all stages in all the study sites during the reproductive season with no records of reproductive females disappearing far from the coast, which means there was no reproductive migration towards estuaries to hatch larvae. Other evidence relies on the presence of the ovigerous females during high water or rainy months in the river inhabited by adults, which is a reverse pattern from the pattern described by Bauer (2013).…”
Section: Reproductionmentioning
confidence: 94%
“…These recruits can be captured during their migration to colonize or re-colonize riverine habitats. Commonly, the low speed of the water flow in dry seasons benefits the presence of recruits due to low amount of energy required to move upstream associated to few potential obstacles for re-colonization (e.g., reduced downstream drift) (Bauer 2004(Bauer , 2013. There were no recruitment data for P. pandaliformis in other locations, which prevents any comparisons.…”
Section: Sex Ratio and Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These works were focused in terms of swimming speed (m.s -1 ) and swimming endurance (s). Otherwise, [20] studied the effect of effort in swimming on glucose levels in lymph freshwater prawn. The aforementioned aspects of these works done were taken into account in order to have a better sizing migration step for river prawn and reduce to a minimum the effect of their migratory movement.…”
Section: Hydraulic Modeling Of Prawn Stepmentioning
confidence: 99%
“…This indicates a diadromous strategy with larval export to salt water, followed by larval development in estuarine or coastal marine water, and finally an upstream migration and recolonization of limnic habitats by juveniles (for recent review of reproductive strategies in freshwater shrimp, see Bauer, 2013). Since unfavorable osmotic conditions may cause enhanced metabolic losses, and thus, reduced larval survival and growth (McNamara et al, 1983;Zanders & Rodríguez, 1992;Huong et al, 2010), this raises the question which salinities allow for successful rearing in research cultivation and commercial aquaculture.…”
Section: ____________________mentioning
confidence: 99%